LAPAROSCOPIC CHROMOPERTUBATION FOR THE EVALUATION OF TUBAL PATENCY IN DAIRY CATTLE - SOFI, K A; SINGH, M; KUMAR, P; SHARMA, A (The Indian Journal of Animal Reproduction, 2022)
The present study was conducted to evaluate feasibility of laparoscopic chromopertubation using methylene blue dye as a tubal patency test in bovines. This test was done during routine laparoscopic examination of dairy cattle (n=5). Laparoscopy was done through left flank and blood / serum samples were collected for hematology, biochemical and hormone analysis at pre- (1 h) and post- (1 and 24 h) laparoscopic procedure. For evaluating tubal patency, Foley’s catheter was inserted into the right uterine horn, fixed and about 30-40 ml autoclaved dilute methylene blue dye (2.5%) was then administered into the horn. The passage of dye through the fallopian tube was observed and appearance of blue color in the oviduct and spillage of dye through the fimbrial end was indicative of patency. The same procedure was repeated on left uterine horn to determine patency. The procedure was successfully done in four cattle and out of these, the left oviduct was blocked at utero-tubal junction only in one cattle. Pre- and post-laparoscopy, the hematological and serum enzyme parameters remained similar (p>0.05), however, serum cortisol was elevated at 1 h post-laparoscopy (p<0.05), which reached pre-laparoscopy concentrations by 24 h post-laparoscopy. Per-rectal examination about two months after procedure revealed uneventful recovery with no adverse impact in genital tract. To our knowledge, it is the first report on laparoscopic chromopertubation for tubal patency evaluation in bovines. In conclusion, laparoscopic chromopertubation using methylene blue dye is safe and innocuous procedure and can be used for evaluation of tubal patency in bovines in the future, but it needs further study and validation especially for impact on fertility.